2009
DOI: 10.3354/meps07896
|View full text |Cite
|
Sign up to set email alerts
|

Piscivore assemblages and predation pressure affect relative safety of some back-reef habitats for juvenile fish in a Caribbean bay

Abstract: An important process thought to drive habitat selection during (post-)settlement of coral reef fish is predation. It is assumed that in back-reef habitats such as seagrass beds and mangroves predation is lower than on coral reefs. However, recent studies have suggested that significant piscivore assemblages are present in back-reef habitats. The assumption of reduced predation pressure in back-reef habitats can therefore be debated. We compared piscivore assemblages along the coast of a Caribbean island using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Dorenbosch et al (2009) showed a similar degree of predation risk of early juveniles in bay habitats along a spatial gradient from the mouth of the bay. Therefore, predation risk is unlikely to act as the sole mechanism driving ontogenetic habitat shifts within the bay at this life stage.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Dorenbosch et al (2009) showed a similar degree of predation risk of early juveniles in bay habitats along a spatial gradient from the mouth of the bay. Therefore, predation risk is unlikely to act as the sole mechanism driving ontogenetic habitat shifts within the bay at this life stage.…”
Section: Discussionmentioning
confidence: 91%
“…Natural predators of H. flavolineatum can be diverse, but typically include large juvenile and adult predator fish species. At Cura莽ao, these include Ocyurus chrysurus and Lutjanus apodus in bay environments, while Aulostomus maculates is a common predator on the reef (Dorenbosch et al 2009). The risk of predation is highest during the nocturnal and dusk periods compared to diurnal periods (Danilowicz & Sale 1999).…”
Section: Model Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no significant predation of lionfish has been documented in the Atlantic, the large predators (e.g., serranids) that may occasionally consume lionfish (Maljkovi膰 et al 2008) are typically rare in estuarine systems compared to coral reefs (Dorenbosch et al 2009). The most abundant estuarine predators (e.g., juvenile lutjanids and carangids)…”
Section: Discussionmentioning
confidence: 99%